Tribological and Corrosion Effects from Electrodeposited Ni-hBN over SS304 Substrate - Suresh Velayudham; Elango Natarajan; Kalaimani Markandan; Kaviarasan Varadaraju; Santhosh Mozhuguan Sekar; Gérald Franz; Anil Chouhan (Lubricants)
The aim of the present study is to investigate the influence of Nickel–Hexagonal Boron Nitride (Ni-hBN) nanocomposite coatings, deposited using the pulse reverse current electrodeposition technique. This experimental study focuses on assessing the tribological and corrosion properties of the produced coatings on the SS304 substrate. The microhardness of the as-deposited (AD) sample and heat-treated (HT) sample were 49% and 83.8% higher compared to the control sample. The HT sample exhibited a grain size which was approximately 9.7% larger than the AD sample owing to the expansion–contraction mechanism of grains during heat treatment and sudden quenching. Surface roughness reduced after coating, where the Ni-hBN-coated sample measured a roughness of 0.43 µm compared to 0.48 µm for the bare surface. The average coefficient of friction for the AD sample was 42.4% lower than the bare surface owing to the self-lubricating properties of nano hBN. In particular, the corrosion rate of the AD sample was found to be 0.062 mm/year, which was lower than values reported in other studies. As such, findings from the present study can be particularly beneficial for applications in the automotive and aerospace industries, where enhanced wear resistance, reduced friction, and superior corrosion protection are critical for components such as engine parts, gears, bearings and shafts.